Biofuel supply chain management in the circular economy transition: An inclusive knowledge map of the field. (June 2022) - Ranjbari, Meisam; Shams Esfandabadi, Zahra; Ferraris, Alberto; Quatraro, Francesco; Rehan, Mohammad; Nizami, Abdul-Sattar; Gupta, Vijai Kumar; Lam, Su Shiung; Aghbashlo, Mortaza; Tabatabaei, Meisam
Abstract: Investment in biofuels, as sustainable alternatives for fossil fuels, has gained momentum over the last decade due to the global environmental and health concerns regarding fossil fuel consumption. Hence, effective management of biofuel supply chain (BSC) components, including biomass feedstock production, biomass logistics, biofuel production in biorefineries, and biofuel distribution to consumers, is crucial in transitioning towards a low-carbon and circular economy (CE). The present study aims to render an inclusive knowledge map of the BSC-related scientific production. In this vein, a systematic review, supported by a keywords co-occurrence analysis and qualitative content analysis, was carried out on a total of 1, 975 peer-reviewed journal articles in the target literature. The analysis revealed four major research hotspots in the BSC literature, namely (1) biomass-to-biofuel supply chain design and planning, (2) environmental impacts of biofuel production, (3) biomass to bioenergy, and (4) techno-economic analysis of biofuel production. Besides, the findings showed that the following subject areas of research in the BSC research community have recently attracted more attention: (i) global warming and climate change mitigation, (ii) development of the third-generation biofuels produced from algal biomass, which has recently gained momentum in the CE debate, and (iii) government incentives, pricing, and subsidizing policies. The provided insights shed light on the understanding of researchers, stakeholders, and policy-makers involved in the sustainable energy sector by outlining the main research backgrounds, developments, and tendencies within the BSC arena. Looking at the provided knowledge map, potential research directions in BSCs towards implementing the CE model, including (i) integrative policy convergence at macro, meso, and micro levels, and (ii) industrializing algae-based biofuel production towards the CE transition, were proposed. Graphical abstract: Image 1 Highlights: The findings revealed four major research hotspots in the BSC domain. Algal biofuels have recently gained momentum in the circular economy (CE) debate. Integrative policy convergence is needed to link bioeconomy with the CE. Future research avenues for BSC management towards the CE transition were proposed.